Genetic variability in HPV 33 and 35 E6 and E7 genes from South African and Mozambican women with different cervical cytology status - Cremildo Maueia; Alltalents T. Murahwa; Olivia Carulei; Ongeziwe Taku; Zizipho Mbulawa; Alice Manjate; Ziyaad Omar Valey; Tufária Mussá; Anna-Lise Williamson (Virology Journal)
Abstract Background Among the high-risk human Papillomavirus (hr-HPV) genotypes related to cervical cancer (CC) cases, HPV16 and 18 are the most studied worldwide. However, several studies have identified HPV 33 and HPV 35 as some of the most common genotypes in sub-Saharan African regions. This study aims to investigate the genetic variability and lineages of HPV 33 and 35 based on the HPV E6 and E7 genes in isolates from South African and Mozambican women with different cervical cytology statuses. Methods The study analysed 26 HPV 33 and 46 HPV 35 DNA samples collected previously from South African and Mozambican women. The E6 and E7 genes were amplified by polymerase chain reaction (PCR) using genotype-specific primers. Sequences were mapped to the reference sequences using Qiagen CLC Genomics Workbench software and aligned with the HPV 33 and 35 lineages reference sequences. Single nucleotide polymorphisms (SNPs) in the E6 and E7 genes were identified, and the phylogenetic trees were generated. Results Of the 26 HPV 33-positive subjects, 62% (16/26) were from women with high-grade squamous intraepithelial lesions (HSILs). Phylogenetic analysis revealed that 38% (10/26) of the isolates clustered with European lineages. Specifically, 30% (8/26) of isolates clustered in the A1 sublineage, and 8% (2/26) in the A2 sublineage. The African 1 lineage (B1 sublineage) was identified in 19% (5/26) of the isolates. Notably, 42% (11/26) of the isolates did not cluster with any of the reference sequences under investigation, through E6 and E7 genes analysis. In the HPV 33 E6 gene, 80 SNPs were identified and 30 in the E7, frequently in the HSILs subjects. Of the 46 HPV35-positive subjects, 46% (21/46) were from women with HSILs, and 43% (20/46) of the isolates clustered with the European lineages. Specifically, 39% (18/46) clustered to the A1 sublineage, and 4% (2/46) clustered to the A2 sublineage. However, 4% (2/46) of the isolates did not cluster with any of the study sublineage. Seven SNPs were detected in the E6 region and two in the E7 region of the HPV 35 isolates. Conclusion The present study’s genetic analysis showed a higher prevalence of European HPV 33 and 35 variants. Fewer SNPs were found in the studied genes of HPV 35 isolates. The addition of HPV 35 to the HPV vaccines would result in improved cervical cancer prevention. The study findings contribute to a better understanding of the genetic diversity of the HPV circulating in Southern African women and may inform strategies for cervical cancer prevention, including the design of therapeutic vaccines for women in advanced cytological disease stages.